1986
DOI: 10.1103/physrevlett.56.2364
|View full text |Cite
|
Sign up to set email alerts
|

ReactionC12(e,ep)

Abstract: The reaction n C{e,e'p) in the dip region (o> = 200 MeV, q = 400 MeV/c) has been measured in parallel kinematics for missing energies up to 160 MeV. A coincidence yield considerably larger than that expected for a one-body reaction process is observed, though the one-body contribution from p-and s-shell knockout is also present. A uniform continuum strength extends from beyond the p shell to the highest measured missing energies. This continuum strength is the dominant contribution to the (e,e f p) reaction pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

1987
1987
2003
2003

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 11 publications
2
35
0
Order By: Relevance
“…See text for details. [25][26][27][28]43]. The regions marked with an asterisk indicate the two measurements of this paper.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…See text for details. [25][26][27][28]43]. The regions marked with an asterisk indicate the two measurements of this paper.…”
Section: Discussionmentioning
confidence: 99%
“…The regions marked with an asterisk indicate the two measurements of this paper. [25][26][27][28]43]. The data-theory-ratio is given by the measured cross section integrated over the peak in missing energy, divided by the DWIA calculation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…: i) the y-scaling analysis [2] of inclusive (e, e ′ ) experiments [3] has clarified the link between P (k, E) and the nucleon momentum distribution n(k); ii) the high-resolution A(e, e ′ p)X experiments have shown that the shell-model occupation numbers can be substantially less than one, which is a clear signature of the breakdown of the mean field picture [4]; iii) the exclusive A(e, e ′ p)X experiments on A = 3 and A = 4 nuclei, performed in kinematical regions corresponding to high excitation energies of the residual nuclear system, have given the first direct signature of the effects of NN correlations on P (k, E) [5,6]; iv) the recent data on the process 12 C(e, e ′ p)X have raised the question of multi-nucleon emissions generated by NN correlations [7,8]. The above experimental information clearly indicates that the single-particle strenght is not concentrated uniquely at low values of k and E (as it is the case within a mean field picture), but, due to short-range and tensor NN correlations, is spread over a wide range of nucleon momenta and removal energies.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, other processes beyond the simple one-body mechanism become important above the threshold of two-nucleon emission and in the socalled dip-region, i.e. in the region between the QF peak and the ∆-resonance excitation [8,9].…”
Section: Introductionmentioning
confidence: 99%